Refugee Management in the National Security Dimension: A Comparative Study in Indonesia, Malaysia, and Thailand - M. Alvi Syahrin; Tony Mirwanto; Budy Mulyawan; Arief Febrianto; Rita Kusuma Astuti (Journal Evidence Of Law, 2025)
This study comparatively analyzes refugee management models in Indonesia, Malaysia, and Thailand—three key ASEAN frontline states that have not ratified the 1951 Refugee Convention. It investigates how this humanitarian issue has been securitized and integrated into their national security frameworks. Refugee movements, dominated by populations like the Rohingya, have evolved from a humanitarian crisis into a regional security challenge involving sovereignty, border control, human smuggling, and domestic social cohesion risks. Due to the lack of a binding international legal structure, these countries rely on ad hoc and discretionary approaches, dictated by internal political and geopolitical calculations. Using a qualitative-comparative methodology based on securitization theory, the research reveals significant variation in implementation. Indonesia attempts to balance humanitarian efforts (via IOM/UNHCR) with sovereignty concerns, viewing management as an issue of maritime security and public order. Conversely, Malaysia demonstrates the highest level of securitization, explicitly linking refugees to immigration violations and economic/health threats, with harsh law enforcement as the primary measure. Thailand employs a 'pragmatic border control' model, treating refugees as a short-term immigration matter susceptible to domestic military and political interests. This demonstrates a dominant security logic prioritizing national interests and rationalizing the rejection of non-refoulement. The main conclusion is that the failure to establish a binding regional burden-sharing mechanism encourages states to shift responsibility to the security domain, exacerbating refugee vulnerability and empowering smugglers. An urgent ASEAN policy shift toward a legal-institutional protection framework is required.